PENGARUH FAKTOR NON TEKNIS PERTANDINGAN DALAM PENILAIAN JURI KEPADA ATLET PENCAK SILAT - Wahyudi, Achmad Rizanul; Natalia, Adinda Ayu (Journal of Sport and Exercise Science, 2021)
The judging process which is considered closed is able to give distorted thoughts from the coaches and athletes of pencak silat. Some argue that there are other factors that can influence the judges' judgment when judging athletes. Based on the explanation above, the researchers made a study entitled "The Influence of Non-Technical Competition Factors in Jury Assessments of Pencak Silat Athletes". The purpose of this research is to find out whether there is an influence of non-technical competition on the jury's assessment of pencak silat athletes and to determine the percentage level of influence of non-technical factors on the jury's assessment of pencak silat athletes. This research is a type of quantitative research with a descriptive survey approach with non-experimental methods. The data was obtained through the distribution of questionnaires or questionnaires with written questions distributed among the pencak silat judges and 38 respondents from active judges in the city of Surabaya. The results showed that the level of integrity of the judges of Surabaya City was still relatively high because there were 25 people occupying the high category with a percentage of 68% and 13 people occupying the medium category with a percentage of 34 - 67%. In addition, the results of the study also showed that facilities and infrastructure were also able to influence the performance of the judges of the Surabaya City with 20 people in the high category with a percentage rate of 72%, while 18 people in the medium category with a percentage rate of 37-71%. From the results of these three indicators, namely integrity, facilities and infrastructure, as well as understanding the rules of the game, each has an influence in the high category percentage.